Femtosecond dark-field imaging with an X-ray free electron laser - Martin, Andrew; Epp, Sascha W.; Erk, Benjamin Michael Dieter; Foucar, Lutz Michael; Kassemeyer, Stephan; Lomb, Lukas; Rolles, Daniel; Rudek, Benedikt; Rudenko, Artem; Shoeman, Robert L.; Steinbrener, Jan; Ullrich, Joachim; et al. (Optics express, 2012)
The emergence of femtosecond diffractive imaging with X-ray lasers has enabled pioneering structural studies of isolated particles, such as viruses, at nanometer length scales. However, the issue of missing low frequency data significantly limits the potential of X-ray lasers to reveal sub-nanometer details of micrometer-sized samples. We have developed a new technique of dark-field coherent diffractive imaging to simultaneously overcome the missing data issue and enable us to harness the unique contrast mechanisms available in dark-field microscopy. Images of airborne particulate matter (soot) up to two microns in length were obtained using single-shot diffraction patterns obtained at the Linac Coherent Light Source, four times the size of objects previously imaged in similar experiments. This technique opens the door to femtosecond diffractive imaging of a wide range of micrometer-sized materials that exhibit irreproducible complexity down to the nanoscale, including airborne particulate matter, small cells, bacteria and gold-labeled biological samples.
Published 31 May 2012
Gesehen am 19.09.2018